Activity identification and tracking - Koninklijke Philips, N. V. (2018)
In an embodiment , a wearable device ( 12 ) is disclosed that automates the detection and determination of a type of activity , and both measures physiological and behavioral parameters and computes information corresponding to measured physiological parameters based on the determined type of activity . An embodiment of the wearable device provides these features by wirelessly receiving a signal with information coded therein that enables the wearable device to automatically detect and identify the type of activity in which a person ( 82 ) is engaged . The determination of the type of activity enables a more accurate computation of information that is specific to the activity in which the person is engaged , the computation of information based on the measured physiological and behavioral parameter .